Recommendations for High-Stakes Examinations for Public Malaysian Medical Faculties during the COVID-19 Pandemic - Kamarul Aryffin Baharuddin; Ahmad Fuad Abdul Rahim; Yang Faridah Abdul Aziz; Roslina Abdul Manap; Ahmad Marzuki Omar; Nariman Singmamae; Salwani Ismail; Effat Omar; Fairrul Kadir; Norhafizah Mohtarrudin; Mohd Azhar Mohd Noor; Muhd Al-Aarifin Ismail; et al. (Penerbit USM, 2024)
Indexed by MYCITE